The Relationship Between the Duration of Gadget Use and Emotional and Hyperactivity-Inattention Behavior in Adolescent - Azzahara, Andi Nurul Hidaya; Rimayanti, Ulfah; Wiyata Gama, Arlina; Trisnawaty (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Backgrounds Adolescence is a physical and mental development period that various factors could influence. Aims This research aims to determine the relationship between the duration of gadget use and emotional symptoms and hyperactivity disorder in adolescents. Methods This research is a cross-sectional study with a quantitative approach using the Strengths & Difficulties Questionnaire (SDQ) to determine adolescents’ emotional and hyperactivity-inattention behavior. This research is a correlational study in which 142 students at SMA Negeri 4 of Wajo Regency selected as research subjects. We analyze research data using the Chi-Square test with a significance level of 5%. Results The results of the Chi-Square test indicate that the p-value amount to 0.062 (emotional symptoms) and 0.170 (hyperactivity disorder). Emotional symptoms and hyperactivity-inattention indicate a p-value of >0.05 (more than 0.05). Conclusion From this research, there are differences between groups with different duration of gadget use and emotional symptoms, as well as groups with different duration of gadget use and hyperactivity-inattention in adolescents, but they were statistically insignificant.